2022
DOI: 10.1002/hsr2.481
|View full text |Cite
|
Sign up to set email alerts
|

“An antibiotic turned contraceptive”: The tale of ampicillin‐cloxacillin

Abstract: Antibiotic misuse is a major public health threat globally, requiring active efforts toward halting its progression. The African sub‐region is worst hit by communicable diseases, and also possesses weak health systems to effectively combat the menace of antimicrobial resistance. Meanwhile, antibiotics are among the most regularly misused medicines in Nigeria, particularly for inappropriate indication and duration. This is seen in its use as a contraceptive by young women in the country. This paper evaluates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“… 34 A previous study in Nigeria reported poor knowledge of appropriate OTC selection and OTC-related side effects among some drug vendors. 35 High prevalence of OTC medicines misuse was also observed in previous studies in Nigeria, 36 , 37 suggesting more attention on provision of OTC medicines advice and counselling by pharmacy personnel. Meanwhile, drug information is a recognized service in community and hospital pharmacies.…”
Section: Discussionsupporting
confidence: 61%
“… 34 A previous study in Nigeria reported poor knowledge of appropriate OTC selection and OTC-related side effects among some drug vendors. 35 High prevalence of OTC medicines misuse was also observed in previous studies in Nigeria, 36 , 37 suggesting more attention on provision of OTC medicines advice and counselling by pharmacy personnel. Meanwhile, drug information is a recognized service in community and hospital pharmacies.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, they also cause some side effects, such as allergic reactions and disruption of the gut microbiome. [ 142 ] Thus, it is critical to develop new antimicrobial methods with high safety, less allergic reactions, precise targeting, and low risk of bacterial resistance.…”
Section: Biomedical Applications Of Sazymesmentioning
confidence: 99%
“…Antibiotics are sold over the counter, in public buses and open markets resulting in antibiotic abuse and misuse leading to resistance. In Nigeria, ampicillin and cloxacillin (ampiclox) is been abused by young girls as contraceptives after sex [36]. Antibiotics are also abused by both men and women, usually ampiclox 500mg start, is taken after unprotected sex in Nigeria for prevention of infection.…”
Section: Causes Of Antimicrobial Resistancementioning
confidence: 99%